(untitled) (Journal of Scientific Research, 2013)
The study was carried out for 138 days to know the growth and survival rate of P. monodon by applying probiotics in Gazi Fish Culture Ltd. Dacope, Khulna, Bangladesh. Six experimental ponds (4000 m2 in size i.e. one acre) were selected of which three were probiotic ponds and three were controlled. After pond preparation, PL15 (average weight of each 4.75±0.09 g) was stocked at the rate of 13 per m2 following polymerase chain reaction (PCR) test. CP NASA shrimp feed was used during the study period. Transparency, salinity, pH, dissolved oxygen (DO), temperature, total Ammonia Nitrogen (TAN) were recorded by standard measurements. The average final body weight of the harvested shrimp is 37.67±1.15 g in probiotics ponds and 27.33±0.58 g in controlled ponds and the difference was significant (P < 0.01) between these two productions. The average survival rate was 90.67±1.15 % in probiotic pond and 71.00±3.0 % in controlled pond. The average daily gain (ADG) in weight was 0.27±0.01 g and 0.19±0.01 g in probiotic and controlled ponds, respectively. The result showed that probiotic plays an important role in maintaining water quality parameters, soil quality and health management as well as increases the growth and survival of shrimp. Key words: Probiotics; P. monodon; Water quality parameter; Growth rate; Survival rate. © 2013 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v5i2.11815 J. Sci. Res. 5 (2), 363-370 (2013)